EKSPLORASI MODEL PENERIMAAN TEKNOLOGI DALAM MEMBENTUK NIAT MENGGUNAKAN KEMBALI APLIKASI KESEHATAN - Didik Setyawan; Ariefah Yulandari; Diah Ayu Anggraini; Nang Among Budiadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The application of Technology Acceptance Model in the use of health applications requires development. This study examines the development of an extended Technology Acceptance Model by adding the variables of convenience, perceptual disturbance, and self-efficacy. Respondents in this study were users of the Halodoc health application, as many as 250 respondents were selected based on purposive random sampling. Hypotheses testing were carried out using SEM (Structural Equation Modeling) analysis with the AMOS method which resulted in seven supported hypotheses and two unsupported hypotheses, namely perceptual disturbances which had no effect on perceived usefulness and perceived ease of use. The test results indicate the intention to reuse the Halodoc health application because the user gives a positive attitude towards the health application. The high positive attitude is due to the user's perception that health applications provide ease of use and usefulness in their use which are formed by convenience and self-efficacy, not because of disturbances perceived by application users. The implication of the results of the study is the need to provide convenience in use and provide confidence for users that the application is easy to use and useful, thereby increasing attitudes and intentions to continue using.